The systemic approach on deterministic view of social change - Shogar, Ibrahim (2020)
Background: Understanding the principal causes of ‘change’ in social phenomena, and predicting its future directions is necessary for change management and controlled social development. The complex nature of the field, however, has been the major problem to achieving this noble goal. The present paper presupposes that smart application of principles of systems biology on social phenomena can contribute in addressing the two major problems of ‘change management’ in social sciences, which are prediction and control. Objective: This paper aims to explore how application of principles of systems biology on social phenomenon can contribute to address the above two problems of change management. The method of physical sciences has been successful in introducing mankind to understand changes of material world due to its measurable conclusions. However, philosophers of sociology are still facing challenges to deal with the most fundamental questions of the field, such as the nature of the governing principles of social change and how it can contribute for better change management? Methodology: The method adopted in the paper is theoretical and analytical in nature. Principles of systems biology will be investigated and formulated. The gap between physical and social sciences is increasingly collapsing due to conclusions of Quantum Mechanics, thus, this paper adopts the integrated method of analysis. The paper, also, analyzes the key concepts, such as “social change” and “systems biology”. The various perspectives of sociologists, anthropologists, and philosophers of social sciences will be presented. Results & Conclusions: The paper concludes that for proper management of social change, social scientists need sufficient data on social phenomena, mathematics, and effective technologies for analysis. Application of systems biology can assist on this part. The paper, also, suggests that understanding the governing principles of social phenomena, such as cultures, norms, religion and moral values, is necessary to predict the future directions of social change.